Surface textures and friction control in microforming - Castagne, Sylvie (2014)
Tribological surface textures are considered in this paper as a non-traditional friction control solution for microforming. Textured pads fabrication techniques are first evaluated and load-controlled micro-embossing is chosen as the optimal method to produce repeatable textured patterns on metallic pads. Using tribometer experiments and finite element simulations of dry contact between untextured and textured surfaces for pressure levels representative of microforming conditions, it is shown that there are competing mechanisms creating a sinusoidal-like friction reduction behavior when surface textures are present. Ultimately, it is concluded that a proper design of surface textures and loading conditions can be used for friction reduction in microforming.